Development and validation of a rapid RP-HPLC method for simultaneous quantification of paclitaxel and cetuximab in immunoliposomes - Souza, Ana Luiza Ribeiro de; Amorim, Amanda Cláudia Ferreira; Cintra, Emílio Ramos; Ferreira, Natália Noronha [UNESP]; Silva, Luís Antônio Dantas; Hayasaki, Tacio Gonçalves; Diniz, Danielle Guimarães Almeida; Lima, Eliana Martins (Elsevier, 2021)
The development of rational therapies against complex diseases, such as cancer, has increased in the past few years due to the advances of ‘omics’ technologies. Concomitantly, several efforts have been made to design sophisticated drug delivery systems in order to increase specificity and drug accumulation in tumor sites. The complexity of these drug delivery systems highlights the need for suitable analytical methods to determine encapsulation/conjugation efficiency of drugs and molecules responsible for the targeted delivery. Therefore, this study focuses on the development and validation of a RP-HPLC-DAD methodology for concurrent quantification of paclitaxel (PTX) and cetuximab (CTX) in immunoliposomes. Chromatographic separation was achieved using a wide pore C8 column, and a gradient mobile phase consisting of 0.1% trifluoroacetic acid (TFA) in Milli-Q water/acetonitrile/isopropanol with a flow rate of 1 mL min−1. Drug peaks were fully separated and detected at 280 nm using UV detector. The method was validated according to ICH and FDA guidelines in terms of specificity and forced degradation studies, system suitability, linearity, limit of detection, limit of quantification, repeatability, intermediate precision, accuracy, robustness, and short-term stability. The developed method was linear over the concentration range of 37.5–150 μg mL−1 of PTX and 75–300 μg mL−1 of CTX. All parameters evaluated satisfied the acceptance criteria, according to both FDA and ICH guidelines. The applicability of the analytical method was assessed following the development of PTX-loaded immunoliposomes conjugated with CTX. Thus, the present study shows a novel, simple, stability-indicating and suitable method to quantify simultaneously PTX and CTX in immunoliposomes.
Keywords: Antibody targeting; Breast cancer; Multifunctional liposomes; Nanomedicine; Surface modified liposomes; Theranostic liposomes